Impact of first- and second-line treatment for Hodgkin’s lymphoma on the incidence of AML/MDS and NHL—experience of the German Hodgkin’s Lymphoma Study Group analyzed by a parametric model of carcinogenesis - Scholz, M.; Engert, A.; Franklin, J.; Josting, A.; Diehl, V.; Hasenclever, D.; Loeffler, M. (Annals of oncology, 2011)
Using a parametric carcinogenesis model, we disentangle the superimposing effects of primary and relapse therapies of Hodgkin's disease on secondary neoplasias. We analyze eight randomized trials of the German Hodgkin's lymphoma study group [5357 individuals, 67 secondary acute myeloid leukemia (AML)/myelodysplastic syndrome (MDS) and 97 secondary non-Hodgkin’s lymphoma (NHL)]. Primary therapies were divided into four groups: radiotherapy alone, moderately dosed COPP/ABVD-like chemotherapies for intermediate and advanced stages and BEACOPP escalated. For secondary AML/MDS, the hazards after primary therapies are proportional (maximum at 3.4 years), while the hazard after relapse therapy is more peaked (maximum at 1.8 years). Intermediate and advanced stage chemotherapy resulted in a cumulative risk of 1.5%, while the risk after BEACOPP escalated is higher (4.4%, P = 0.004) and comparable with that after relapse therapy (4.5%). For secondary NHL, there are no differences in cumulative risk between the primary therapies (2.9%), while the risk after relapse therapy is increased (6.6%, P = 0.002). BEACOPP escalated moderately increases the risk of secondary AML/MDS but not NHL. No differences were found between other chemotherapies of advanced stages and intermediate stages. Secondary AML/MDS occurs faster after relapse treatment than after primary treatment.